(untitled) (Revista Argentina de Cirugía, 2025)
Background: The assessment of patients admitted to a surgical ward includes preoperative and postoperative monitoring and complications and represents a challenge for postgraduate year-1 residents due to their limited experience and heavy workload. A system for categorizing patients according to clinical and laboratory parameters could be useful. We propose the use of a color-coded scale based on patient’s severity. Although there are categorization systems similar to the one proposed, they have not been described for surgical wards. Objective: The aim of this study was to determine the feasibility and acceptance of a color-coded categorization system for hospitalized patients in a general surgical ward. Material and methods: We conducted a prospective, descriptive, and observational study (JanuaryMarch 2024) in a surgical ward. We included all patients hospitalized who had no limitations of lifesustained treatment. We elaborated a chromatic scale based on clinical parameters, pain scale and intraoperative adverse events, where green indicates mild cases, yellow indicates moderate cases, and red indicates serious cases. The residents evaluated the system through a self-administered survey. Results: A total of 3693 patients (3436 green, 253 yellow, and 4 red) were evaluated by seven postgraduate year-1 residents. Thirty (11.86%) patients initially classified as green were subsequently re-categorized as yellow and no yellow patients were moved to the red category. All the patients initially classified as yellow were subsequently re-categorized as green, while three patients initially classified as red were first moved to the yellow category and then to the green category.